Dehydration stress extends mRNA 3′ untranslated regions with noncoding RNA functions in Arabidopsis - Sun, Hai-Xi; Li, Yan; Niu, Qi-Wen; Chua, Nam-Hai (Genome Research, 2017)
The 3′ untranslated regions (3′ UTRs) of mRNAs play important roles in the regulation of mRNA localization, translation, and stability. Alternative cleavage and polyadenylation (APA) generates mRNAs with different 3′ UTRs, but the involvement of this process in stress response has not yet been clarified. Here, we report that a subset of stress-related genes exhibits 3′ UTR extensions of their mRNAs during dehydration stress. These extended 3′ UTRs have characteristics of long noncoding RNAs and likely do not interact with miRNAs. Functional studies using T-DNA insertion mutants reveal that they can act as antisense transcripts to repress expression levels of sense genes from the opposite strand or can activate the transcription or lead to read-through transcription of their downstream genes. Further analysis suggests that transcripts with 3′ UTR extensions have weaker poly(A) signals than those without 3′ UTR extensions. Finally, we show that their biogenesis is partially dependent on a trans-acting factor FPA. Taken together, we report that dehydration stress could induce transcript 3′ UTR extensions and elucidate a novel function for these stress-induced 3′ UTR extensions as long noncoding RNAs in the regulation of their neighboring genes.